Benefits of bloodletting procedure among Bad-mKhris-mGo-Nad patients: A prospective observational study - Karma Ugyen; Karma Tenzin; Tempa Gyeltshen (Bhutan Health Journal, 2021)
Introduction: Bad-mKhris-mGo-Nad is a type of headache caused by imbalance of bile and phlegm humor. In gSo-ba-Rig-pa, headache is categorized in two categories such as primary headaches and secondary headaches. In total there are 14 types of headaches and Bad-mKhris-mGoNad is one among the principal headaches. The gSo-ba-Rig-pa based bloodletting therapy for Bad-mKhris-mGo-Nad has been practiced by the traditional medicine practitioners since the inception of gSo-ba-Rig-pa more than 2500 years ago. Bloodletting is also believed to be one of the most important and effective therapy in the treatment regime of gSo-ba-Rig-pa. The Subsequent Tantra (last tantra) states that the bloodletting is the best remedy for all types of bile and blood-related disorders. This study was conducted to observe the effectiveness of bloodletting procedure among diagnosed cases of Bad-mKhris-mGo-Nad.